Polycystic Ovary Syndrome: A Disorder of Reproductive Age, Its Pathogenesis, and a Discussion on the Emerging Role of Herbal Remedies - Zeng, Ling-Hui; Rana, Saba; Hussain, Liaqat; Asif, Muhammad; Mehmood, Malik Hassan; Imran, Imran; Younas, Anam; Mahdy, Amina; Al-Joufi, Fakhria A.; Abed, Shaymaa Najm (Frontiers in Pharmacology, 2022)
Polycystic ovary syndrome (PCOS) is a very common, complex, and heterogeneous endocrine disorder of women that involves a combination of environmental and genetic factors. PCOS affects women of growing age particularly at the early to late reproductive stage (15-35years). Currently, PCOS is affecting 1 in every 10 women worldwide. It is characterized majorly by a raised level of androgens such as testosterone and a large number of ovarian cysts (more than 10) that cause anovulation, infertility, and irregular menstrual cycle. PCOS is also related to other endocrine and metabolic abnormalities such as obesity, hirsutism, acne, diabetes, insulin resistance, glucose impairment. PCOS can be treated with allopathic, ayurvedic, and natural or herbal medications along with lifestyle modifications. Herbal medicines remained in demand for numerous reasons; high cost and side effects associated with the use of allopathic medicine and our traditional norms, which have moved humans to use more herbal products for their health benefits. Estrogenic and non-estrogenic phytochemicals present in various plant species such as; Glycyrrhiza glabra L. [Fabaceae], Aloe vera (L.) Burm. f. [Asphodelaceae], Silybum marianum (L.) Gaertn. [Asteraceae], Serenoa repens (W.Bartram) Small [Arecaceae], Actaea racemosa L. [Ranunculaceae] and Angelica sinensis (Oliv.) Diels [Apiaceae] is effective and harmless. Herbal medicines are found cost-effective, more efficacious, and are a highly esteemed source of management/treatment for PCOS than allopathic medicines. In this literature review, diagnosis, signs, and symptoms, causes of hormonal imbalance, risk factors associated with PCOS, and their management is discussed briefly and the focus was to find out the role of herbal remedies in PCOS management.